2002
DOI: 10.1542/peds.110.2.337
|View full text |Cite
|
Sign up to set email alerts
|

Health Status of Children After Admission for Injury

Abstract: The CHQ provided useful information about the impact of injuries on children and their families over time. Significantly reduced scores in several domains of the CHQ highlight problem areas for injury patients, several of which persist through 6 months of follow-up. Low scores in areas of bodily pain and parental emotional burden suggest that improved management of these problems is required. Additional study of risk factors for persistent problems after injury may suggest ways to improve functional outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 19 publications
2
60
1
1
Order By: Relevance
“…Other studies also found that young injury victims reported a reasonably good long-term health state. 7,33 Aitken et al 16 studied the health state of children after admission for an injury with the child health questionnaire and found that after 6 months, 28% of children reported some limitations, which is somewhat higher than the 21% of admitted children with limitations after 5 months resulting from our research. Because the child health questionnaire measures health over 14 domains, it might be more sensitive for limitations than the EQ-5D, which possibly explains the higher prevalence of limitations.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Other studies also found that young injury victims reported a reasonably good long-term health state. 7,33 Aitken et al 16 studied the health state of children after admission for an injury with the child health questionnaire and found that after 6 months, 28% of children reported some limitations, which is somewhat higher than the 21% of admitted children with limitations after 5 months resulting from our research. Because the child health questionnaire measures health over 14 domains, it might be more sensitive for limitations than the EQ-5D, which possibly explains the higher prevalence of limitations.…”
Section: Discussioncontrasting
confidence: 60%
“…[11][12][13][14][15] Few studies have described the impact of injuries on the health status of children with both minor and major injuries over time with a generic quality-of-life measure. 7,16 This article describes a large follow-up study in injured children who were aged 5 to 14 years and had visited an emergency department in the Netherlands. This study is an extension of an earlier follow-up study on functional outcome of injured people who were aged 15 years and older with a similar design.…”
mentioning
confidence: 99%
“…1,2 In 1998, injuries accounted for 5,189 deaths in U.S. children ages 1 to 15 years (40% of all mortality in this age group). 3 Deaths are the gravest outcome of injury, but they represent only a fraction of the childhood injury burden.…”
mentioning
confidence: 99%
“…Death, the gravest outcome of injury, represents a considerable fraction of severe childhood injury burden [1]. On the other hand, nonfatal injury was the leading cause of both temporary and permanent disability for patients 19 years and younger [2] and which accounted for a major proportion of health service utilization in children.…”
Section: Introductionmentioning
confidence: 99%